Degradation of internal fixation materials based on antibacterial and absorbable silk containing different gentamicin concentrations. (July 2022) - Shi, Chenglong; Liao, Xuqiang; Pu, Xiaobing; Li, Xiushi; Wu, Ruihui; Deng, Donghai; Zhou, Yunfei; Huang, Xingqiu
Adding gentamicin to silk fibroin enhances both the antibacterial performance and degradation rate of silk-based materials. The increased material degradation rate can affect the strength of early internal fixation, resulting in internal fixation failure. This study sought to adjust the gentamicin concentration to control the material degradation rate, thereby better meeting clinical application requirements. The in vitro degradation, water absorption rate, and expansion rate of silk-based materials containing different gentamicin concentrations were studied. A gentamicin-loaded silk-based screw was implanted into the femurs of New Zealand rabbits. Micro-computed tomography was used to measure the screw diameter, which was then used to calculate the degradation rate. The specimens were stained with hematoxylin and eosin and Masson's trichrome. The in vitro results revealed increasing material degradation rates with increasing gentamicin concentration but no significant differences in water absorption rates with different gentamicin concentrations. The degradation rates of gentamicin-loaded (4 mg/g) silk-based rod-like materials were approximately 11.08% at three months in vitro and 9.4% in the animal experiment. The time for complete degradation was predicted from the fitting curve to be approximately 16 months. No inflammatory hyperplasia was observed in bone or soft tissue. The degradation and biocompatibility of the material containing 4 mg/g gentamicin meet clinical application requirements, and previous experimental results demonstrate good antibacterial performance of materials containing this gentamicin concentration.